Recurrent Urinary Tract Infections in Female Patients—A Clinical Review - Flavia Liliana Turcu; Ileana Adela Vacaroiu; Andra Elena Balcangiu-Stroescu; Ana Raluca Mitrea; Daniela Miricescu; Daniela Gabriela Balan; Alina Mihaela Stanigut (Journal of Mind and Medical Sciences, 2025)
Worldwide, urinary tract infections (UTIs) have an increased incidence, especially in women. Recurrent UTIs (rUTIs) appear in less than three months in 80% of the cases, being associated with age, sexual activity, or diabetes mellitus. Antibiotics represent the first line of treatment for rUTIs after the diagnosis based on a positive mid-stream urine (MSU) culture. Alternative therapies including low-dose antibiotic treatment, immunoprophylaxis, cranberry extracts, probiotics, D-mannose, intravesical instillations, methenamine, and estrogens may reduce the recurrence of UTIs in female patients. Multimodal therapy seems to be the future in preventing and treating rUTIs. The main aim of this narrative review is to present the actual therapeutic challenges and the most efficient prophylaxis options in women diagnosed with rUTIs.